Solvent‐free synthesis of 6‐deoxy‐6‐(ω‐aminoalkyl)amino cellulose. Issue 39 (21st June 2016) - Heinze, Thomas; Pfeifer, Annett; Koschella, Andreas; Schaller, Jens; Meister, Frank
ABSTRACT: Cellulose p ‐toluenesulfonic acid esters (TosCell) with degree of substitution (DSTos ) between 0.8 and 1.4 were converted with ethylene diamine or tris (2‐aminoethyl)amine. In contrast to procedures published, the conversion was carried out without any solvent, i.e., the reagent (amines) was used as reaction medium yielding readily soluble products. Moreover, the absence of an additional solvent makes the recycling of both not‐consumed amine and precipitant easy. Recycling experiments proofed the possibility of reusing the isolated ethylene diamine. The DS of 6‐deoxy‐6‐(ω‐aminoalkyl)amino groups is between 0.71 and 0.93, which is in accordance with the functionalization pattern of tosyl cellulose and the ability of amines to displace primary tosylate moieties only. Attention must be paid to the precipitant used for the workup procedure; 13 C NMR measurements revealed a formation of imine structures in case of precipitation with acetone. Precipitation in 2‐propanol did not lead to any side product. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43987. Abstract :